Proof-of-Concept of Electrical Activation of Liposome Nanocarriers: From Dry to Wet Experiments - Caramazza, Laura; Nardoni, Martina; De Angelis, Annalisa; Paolicelli, Patrizia; Liberti, Micaela; Apollonio, Francesca; Petralito, Stefania (Frontiers in Bioengineering and Biotechnology, 2020)
The increasing interest towards biocompatible nanotechnologies in medicine, combined with electric fields stimulation, is leading to the development of electro-sensitive smart systems for drug delivery applications. To this regard, recently the use of pulsed electric fields to trigger release across phospholipid membranes of liposomes has been numerically studied, for a deeper understanding of the phenomena at the molecular scale. Aim of this work is to give an experimental validation of the feasibility to control the release from liposomes vesicles, using nanosecond pulsed electric fields characterized by a 10 ns duration and intensity in the order of MV/m. The results are supported by multiphysics simulations which consider the coupling of three physics (electromagnetics, thermal and pore kinetics) in order to explain the occurring physical interactions at the microscopic level and provide useful information on the characteristics of the train of pulses needed to obtain quantitative results in terms of liposome electropermeabilization. Finally, a complete characterization of the exposure system is also provided to support the reliability and validity of the study.